EXPERIMENTAL RESEARCH OF PROCESSING OF DUMP SAND-CLAY MIXES BY THE CENTRIFUGAL AND SHOCK CRUSHING - V. V. Vorobev; V. F. Odinochko; Y. Y. Guminskiy; K. D. Shishpor (Литьë и металлургия)
Results of experimental research of processing of centrifugal and shock crushing of dump sandy-clay mixes are given. Use of products of processing of received mixes in foundry production and in production of asphalt concrete mixes allows to exclude transportation of the mix to dumping.